Co-occurrence of Immunoglobin A Vaculitis and Immunoglobulin A Nephropathy Suggesting Common Pathogenesis: A Case Report: Co-occurrence of Henoch–Schönlein Purpura and Ig A Nephropathy - Mishra, Sweta; Priyadarshini, Lipsa; Kumar Pradhan, Subal (Journal of Pediatric Nephrology, 2024)
Immunoglobulin A (IgA) vasculitis, also known as Henoch-Schönlein purpura, and IgA nephropathy are two different diseases of the same clinical spectrum. They may occur sequentially in the same patient and exhibit overlapping clinical presentations, immunological characteristics, and pathological features. The clinical presentation and the degree of severity are different for individual cases. In this study, we report a girl who initially presented with Henoch-Schönlein purpura, and on follow-up, renal biopsy was suggestive of IgA nephropathy. Accordingly, this presentation suggests the common pathogenesis of both diseases and the need for long-term follow-up of patients with Henoch-Schönlein purpura.